HIV mortality in sanitary districts of Mexico from 1990 to 2015 - Enrique Bravo-García; Carlos Magis-Rodríguez; Manuel Palacios-Martínez; Noé Guarneros-Soto; Patricia Uribe-Zúñiga (Instituto Nacional de Salud Pública, 2019)
Objective. To analyze the distribution and trends of HIV mortality in the Sanitary Districts (JS) of Mexico. Materials and methods. To calculate crude and standardized mortality rates, official figures of deaths from Instituto Nacional de Estadística y Geografía and population estimates from Consejo Nacional de Población were used. Magnitude, distribution and trends of HIV mortality were analyzed, at the national level, by state and JS, using JoinPoint regression model. Results. From 2008 to 2015, HIV mortality decreased by more than 20%. In the 25 JS with highest mortality, live 11% of the national population, but concentrated 28.6% of the total HIV death, with mortality rates two or more fold than national rate. Conclusions. We identified the 25 JS where actions to reduce HIV mortality in Mexico should be focused. For first time a health problem was analyzed in all JS of Mexico.